Carotenoid Content Test of Drought-Tolerant Inpago Paddy Cultivars to Support National Food Security - Azzahroh, Elsa Qonita; Vardhana, Dustyn Putra; Fendiyanto, Miftahul Huda (MUNISI: Military Mathematics and Natural Sciences, 2025)
Rice (Oryza sativa L.) is one of the staple crops that plays a significant role in national food security in Indonesia. Rice plants require 75% water for growth, however, drought poses a major challenge in the production of cereal crops. Climate change is a contributing factor to drought conditions. Inpago cultivar is an excellent variety suitable for cultivation in dry land in Indonesia. This study examines the carotenoid content in drought-tolerant Inpago rice cultivars to support national food security. The method used was UV-Vis spectrophotometry at 470, 646, and 662 nm wavelengths. The procedures involved sample extraction, separation, measurement, and data analysis. The data obtained showed that the carotenoid content in Inpago 5 was 286.84 mg/g dry weight, Inpago 7 was 131.36 mg/g dry weight, and Inpago 10 was 139.18 mg/g dry weight. It can be concluded that rice with the Inpago 5 genotype represents a new superior variety with high drought tolerance.